Blockchain Based MFA Solution: the use of hydro raindrop MFA for information security on WordPress websites - Aparecido Cardoso, João Antonio; Ishizu, Felipe Takeshi; de Lima, Jeferson Tadeu; Pinto, Jefferson de Souza (Brazilian Journal of Operations & Production Management, 2019)
Goal: The present work aims to present how the use of a blockchain two-factor authentication solution 2FA on a page developed on WordPress can contribute to the information security regarding user authentication. Design/Methodology/Approach: The research method employed is characterized as an exploratory research, since all the analysis is based on the theoretical reference data available on the subject. A field research was carried out in relation to the implementation of the multi-factor authentication plugin Hydro Raindrop MFA, which uses blockchain technology offered by The Hydrogen Technology Corporation and the Project Hydro platform over the Ethereum network. Thus, this paper sought to present and conceptualize some of the technologies used, pointing out their contribution to information security. Results: The main results showed that the use of decentralized technology, such as blockchain and the Hydro Raindrop Plugin, can contribute considerably in the process of user authentication, which may strengthen the safeguard of the information and assets of individuals and organizations by inhibiting or reducing the possibility of successful a hacker attack. This solution is at the forefront of innovation with regard to data security because it uses advanced blockchain technology. It might contribute in a satisfactory way to the preservation of critical data and information that are the core value of many organizations of the industry 4.0. Limitations of the investigation: This research was limited to analyzing how the implementation of the Hydro Raindrop multi-factor authentication solution on a WordPress page can be beneficial to ensure information security. Practical implications: This study’s findings can contribute to entities interested in cybersecurity. As a suggestion for future works, analyses of plugins or similar solutions available on the market in distinct types of websites, or performance comparisons between them, may be relevant to contribute to scientific research. Originality/Value: This work can contribute in an innovative way to scientific research, since it addresses a recently created solution that uses blockchain technology as its basis for a safer method of authentication.